Legume Consumption and All-Cause and Cardiovascular Disease Mortality. (2nd November 2017) - Li, Hua; Li, Jinmeng; Shen, Yegen; Wang, Jie; Zhou, Depu
Abstract : Background . Legume consumption is suggested to have protective effects against cardiovascular disease (CVD) mortality in the general population, but the results have been equivocal. We conducted a meta-analysis of prospective cohort studies to assess the association between legume consumption and risk of CVD mortality and all-cause mortality. Methods and Results . Medline (via Ovid) and EMBASE (via Ovid) databases were searched through April 2017 to identify eligible studies. The two authors independently extracted the data and the adjusted relative risks (RRs) and 95% confidence intervals (CIs) were pooled by using a random-effects model. A total of 6 studies were identified, including the sizes of participants ranging from 23, 601 to 59, 485 with a sum of 21, 8997. Comparing the highest category with the lowest, the pooled RR (95% CI) was 0.96 (0.86–1.06) for CVD mortality and 0.93 (0.87–0.99) for all-cause mortality. Conclusions . Results from the current study show that high legume intakes are associated with lower risk of all-cause mortality. In consideration of the small number of studies, the evidence for assessing relationship between legumes intake and risk of all-cause mortality remains inclusive and warrants further study in the future. Further, consuming legumes does not increase the risk of CVD mortality.